Who says what? the role of the actor’s political position in ideograph construction - Mahfud Anshori,; Pawito,; Sri Hastjarjo, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Previous studies have shown the relationship between ideology and narrative discourse between ideology and narrative discourse in political debates in parliament, protest movements, or discourse in the media that posit ideology and discourse as a single domination relationship but not in network relations. Consequently, the role of political actors in discourse becomes unattractive and is replaced by media studies. It was discovered that ideographs, and word artefacts, link socio-political cognition and political discourse in practice. They also narrate the ideology of political actors in their daily speeches and quotes in different media outlets, with the meanings presented in vast interpretations. However, these interpretative meanings rely on political function and are embedded in the political position. It is assumed that an ideograph serves as an ideological identity in public discourse while the political organisation of the actors determines the interpretative meaning. Therefore, two prominent ideographs in the Omnibus Law discourse on Job Creation, "welfare" and "democracy," were explored to show the "anchored meaning" and describe how ideological identity leads to the creation of ideographic meaning. We analyse the network of the two ideographs using Discourse Network Analysis (DNA) by Philip Leified and Ideographic Analysis (IA). The findings showed that the functional meaning of "welfare" and "democracy" depends on the use of actors in specific discourse. We concluded that the political position of actors in ideographic narratives plays a more dominant role in the relationship between ideology and narratives.